1993
DOI: 10.1002/bin.2360080302
|View full text |Cite
|
Sign up to set email alerts
|

Preparing direct service staff to teach people with severe disabilities: A comprehensive evalution of an effective and acceptable training program

Abstract: In light of the continuing need for residential, direct service staff to be able to teach people with severe disabilities, we comprehensively evaluated a program to train staff in behavioral teaching strategies. The program was developed and evaluated with attention given to recent concerns in the staff management literature regarding shortcomings with staff training research. The training program, involving a maximum of four, 2-hr classroom instruction sessions and three in vivo observation and feedback sessi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 24 publications
0
48
0
Order By: Relevance
“…A practical implication of this finding is that staff members who are promoted (supervisor, staff, and client) in one investigation represents a labor-intensive research strategy; this may be one reason for the relative lack of research on supervisor behavior. The alternative research model used here was to document the effectiveness of staff implementation of target procedures on measures of client welfare before conducting research on supervision of those procedures; our previous research showed that when staff members implemented the teaching procedures targeted in this study with at least 80% proficiency, concomitant gains in clients' skills occurred (Parsons et al, 1993).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A practical implication of this finding is that staff members who are promoted (supervisor, staff, and client) in one investigation represents a labor-intensive research strategy; this may be one reason for the relative lack of research on supervisor behavior. The alternative research model used here was to document the effectiveness of staff implementation of target procedures on measures of client welfare before conducting research on supervision of those procedures; our previous research showed that when staff members implemented the teaching procedures targeted in this study with at least 80% proficiency, concomitant gains in clients' skills occurred (Parsons et al, 1993).…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, lack of proficiency in the use of teaching procedures by direct-service staff has been well documented (Parsons, Reid, & Green, 1993 Goncalves, Iwata, & Chiang, 1983;Page, Iwata, & Reid, 1982 All new direct-service staff at the facility received training in how to teach clients through the Teaching-Skills Training Program (Parsons et al, 1993). Once a staff member had met a performance criterion (80% correct teaching behavior with two client programs), supervisors were expected to monitor his or her teaching at least monthly.…”
Section: Western Carolina Centermentioning
confidence: 99%
See 2 more Smart Citations
“…Increasingly, researchers see on-the-job feedback as a critical component of staff training, and many studies now supplement analog training with on-the-job feedback (e.g., Cooper & Browder, 2001;Fleming & Sulzer-Azaroff, 1989;Jones, Menditto, Geeson, Larson, & Sadewhite, 2001;Parsons & Reid, 1995;Parsons, Reid, & Green, 1993, 1996Spreat et al, 1985;Stevens et al, 1998). One study in particular sought to isolate the component effects of on-the-job feedback.…”
Section: Analog Versus On-the-job Feedbackmentioning
confidence: 97%